Kairo, Ägypten: Die Geschichte der Abteilung Kairo des DAI im Spannungsfeld deutscher politischer Interessen von 1881 bis 1966 - Voss-Kern, Susanne (e-Forschungsberichte des DAI, 2023)
After the publication of the first volume of the history of the DAI Cairo Department (1881 to 1929) research proceeded to the period from 1929 to 1945. From 1920 onwards, there has been a marked increase in international Egyptological publications on Egyptian prehistory. In particular Anglo-Saxon archaeology took a leading rôle in Egypt and in the Middle East. After Hermann Junker took over the position as head of the German Institute in Cairo from Ludwig Borchardt, German scholarship joined this trend. Against the background of ideological discourse, the treatment of Egyptological subjects came into a direct and close relationship to the Nazi view of history on the rise.